INTEGRASI KONTEKS MATEMATIKA DALAM PENGEMBANGAN MODEL LEARNING CYCLE 5E UNTUK MENINGKATKAN PEMAHAMAN KONSEP HUKUM OHM DI SMAN 2 PEUSANGAN - Noviyanti, Noviyanti; Khairunnisak, Kahirunnisak (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study aims to develop a Learning Cycle 5E instructional model integrated with mathematical context to enhance students' conceptual understanding of Ohm’s Law in Grade X at SMAN 2 Peusangan. The research method employed is a model development approach based on a simplified version of Borg & Gall, consisting of four stages: preliminary study, model design, expert validation and revision, and limited trial. The limited trial involved 30 students and was conducted over four sessions. Expert validation results indicated that the developed model is highly valid (87.3%). The limited trial showed an increase in the average conceptual understanding score from 54 (pre-test) to 82 (post-test), with an N-Gain score of 0.61, classified as moderate to high. Data analysis was carried out using descriptive quantitative methods by calculating the N-Gain value and analyzing expert validation results. The integration of mathematical context within the 5E Learning Cycle model effectively assisted students in understanding the conceptual and mathematical relationships between voltage, current, and resistance. Furthermore, the model proved effective in enhancing students' critical thinking and problem-solving skills. Therefore, this model is considered feasible for broader implementation in physics education